Women As Heroine In Shakespeare’S Play: As You Like It: Exploring Gender Roles and Power Dynamics in Shakespeare's As You Like It (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In Shakespeare the male and female character bearprecisely the same relation to each other as they do in nature and in societythey are not equal in prominence or in power but remain subordinate throughout.